Examining the role of climate finance in the Environmental Kuznets Curve for Sub-Sahara African countries - Isaac Doku; Ronney Ncwadi; Andrew Phiri (Cogent Economics & Finance, 2021)
The purpose of this study is to examine the impact of climate finance on pollutant emissions (CO2, CH4 and N2O) for a sample of 19 Sub-Sahara Africa (SSA) countries over the period 2006 to 2017. Our study augments the traditional Environmental Kuznets Curve (EKC) with climate finance and our findings affirm the existence of an inverted U-shaped relationship between per capita income and emissions (i.e. traditional EKC) as well as between climate finance and emissions (Climate finance-induced EKC). We particularly compute turning points of 3,690 (CO2); 5,710 (CH4) and 6,420 (N2O) for per capita GDP levels and 910 million (CO2), 1.2 billion (CH4) and 1. 6 billion (N2O) for climate finance funds. These turning points are above the current averages observed for the SSA countries hence implying that these African countries are not developed enough and neither receive sufficient climate funding to address the challenges arising from climate change.
Keywords: 330; Carbon emissions (CO2); climate finance; Environmental Kuznets Curve (EKC); methane emissions (CH4); nitrous oxide emissions (N2O); pollution haven-halo hypotheses